Oxidative stress and metabolic diseases: Relevance and therapeutic strategies - Manzoor, Muhammad Faisal; Arif, Zaira; Kabir, Asifa; Mehmood, Iqra; Munir, Danial; Razzaq, Aqsa; Ali, Anwar; Goksen, Gulden; Coşier, Viorica; Ahmad, Nazir; Ali, Murtaza; Rusu, Alexandru (Frontiers in Nutrition, 2022)
Metabolic syndrome (MS) is a prominent cause of death worldwide, posing a threat to the global economy and public health. A mechanism that causes the oxidation of low-density lipoproteins (LDL) is associated with metabolic abnormalities. Various processes are involved in oxidative stress (OS) of lipoprotein. Although the concept of the syndrome has been fiercely debated, this confluence of risk factors is associated with a higher chance of acquiring type 2 diabetes mellitus (T2DM) and atherosclerosis. Insulin resistance has been found to play a significant role in the progression of these metabolism-associated conditions. It causes lipid profile abnormalities, including greater sensitivity to lipid peroxidation, contributing to the increased prevalence of T2DM and atherosclerosis. This review aims to cover the most recent scientific developments in dietary OS, the consequence of metabolic disorders, and their most significant clinical manifestations (T2DM and atherosclerosis). It will also emphasize the effects of dietary approaches in alleviating OS in MS.